Perception of Athletes on the Effects of Energy Drinks on Sports Performance in The University of Ilorin - Tosho, Surajudeen (Program Pascasarjana Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the perception of athletes on the effects of energy drinks on sports performance in the University of Ilorin. The respondents for the study were seventy-six athletes who represented the University of Ilorin in the 2014 Nigeria University Games (NUGA) held at Obafemi Awolowo University, Ile-Ife. The research design adopted descriptive research design of the survey type. Researcher designed questionnaire was used for data collection. The findings of the research revealed that consumption of energy drinks does not have any effect on the speed during competitions as perceived by athletes in the University of Ilorin and consumption of energy drinks does not have any effect on sleep disturbances as perceived by athletes in the University of Ilorin. It was concluded that consumption of energy drinks does not have any negative effects on the speed of the athletes in university of Ilorin. It was recommended that coaches, trainers and physical instructors should enlighten their athletes and trainees on the effects of energy drinks on the body.